Cesarean overuse and the culture of care. (20th February 2019) - White VanGompel, Emily; Perez, Susan; Datta, Avisek; Wang, Chi; Cape, Valerie; Main, Elliott
Abstract : Objective: To assess hospital unit culture and clinician attitudes associated with varying rates of primary cesarean delivery. Data Sources/Study Setting: Intrapartum nurses, midwives, and physicians recruited from 79 hospitals in California participating in efforts to reduce cesarean overuse. Study Design: Labor unit culture and clinician attitudes measured using a survey were linked to the California Maternal Data Center for birth outcomes and hospital covariates. Methods: Association with primary cesarean delivery rates was assessed using multivariate Poisson regression adjusted for hospital covariates. Principal Findings: 1718 respondents from 70 hospitals responded to the Labor Culture Survey. The "Unit Microculture" subscale was strongly associated with primary cesarean rate; the higher a unit scored on 8‐items describing a culture supportive of vaginal birth (eg, nurses are encouraged to spend time in rooms with patients, and doulas are welcomed), the cesarean rate decreased by 41 percent (95% CI = −47 to −35 percent, P  < 0.001). Discordant attitudes between nurses and physicians were associated with increased cesarean rates. Conclusions: Hospital unit culture, clinician attitudes, and consistency between professions are strongly associated with primary cesarean rates. Improvement efforts to reduce cesarean overuse must address culture of care as a key part of the change process.